Cost-effectiveness of assisted conception for male subfertility. Issue 6 (June 2015) - Moolenaar, Lobke M.; Cissen, Maarje; de Bruin, Jan Peter; Hompes, Peter G.A.; Repping, Sjoerd; van der Veen, Fulco; Mol, Ben Willem J.
Abstract Intrauterine insemination (IUI), with or without ovarian stimulation, IVF and intracytoplasmatic sperm injection (ICSI) are frequently used treatments for couples with male subfertility. No consensus has been reached on specific cut-off values for semen parameters, at which IVF would be advocated over IUI and ICSI over IVF. The aim of this study was to evaluate the cost-effectiveness of interventions for male subfertility according to total motile sperm count (TMSC). A computer-simulated cohort of subfertile women aged 30 years with a partner was analysed with a pre-wash TMSC of 0 to 10 million. Three treatments were evaluated: IUI with and without controlled ovarian stimulation; IVF; and ICSI. Main outcome was expected live birth; secondary outcomes were cost per couple and the incremental cost-effectiveness ratio. The choice of IVF over IUI with ovarian stimulation and ICSI over IVF depends on the willingness to pay for an extra live birth. If only cost per live birth is considered for each treatment, above a pre-wash TMSC of 3 million, IUI is less costly than IVF and, below a pre-wash, TMSC of 3 million ICSI is less costly. Effectiveness needs to be confirmed in a large randomized controlled trial.